In vitro skin retention and drug permeation study of Tongluo-Qutong rubber plaster by UPLC/UV/MS/MS (Brazilian Journal of Pharmaceutical Sciences, 2022)
Tongluo-Qutong rubber plaster (TQRP), a typical Chinese patent medicine that contains 13 different herbal remedies, is widely used in clinical practice for the treatment of cervical spondylosis and osteoarthritis. However, due to a lack of in vitro transdermal studies, the active ingredients of TQRP have not been fully elucidated. This presents a huge obstacle for quality evaluation, pharmacokinetic studies and clinical safety assessment of TQRP. In this work, a UPLC/UV/MS/MS method was established and validated to evaluate five analytes in TQRP. The validation demonstrated linearity (r > 0.99), specificity (no co-eluting peaks at the retention times of the analytes), and precision (RSD < 15%) within acceptable parameters. A skin permeation study was performed to determine the concentrations of drugs delivered to the dermis. The 24-hour cumulative permeation of ferulic acid, aleo-emodin, emodin and piperine were 303.68, 709.31, 671.06 and 25561.01 ng/cm2, respectively. According to the fitting data of the TQRP active components, skin permeation was mainly due to a combination of passive diffusion and drug release after matrix erosion.